Flood and Food Security in the Benue Valley: Stylized Facts - Iortyer, Dominic; Yio, W. Benjamin (ABUAD Journal of Social and Management Sciences, 2023)
The scientific consensus is that global climatic change is caused by human activities. Global climate variation has altered the pattern of annual rainfall in most parts of the world, resulting in annual flooding with devastating effects on humanity. With many rivers that crisscross the Nigerian landscape, the country has experienced a number of flood incidents along the river basins (valleys) with varying degrees of devastation. This paper, thus, focuses on the effects of flood on food security in the Benue Valley. The specific objectives of the study include: to examine the effects of flood on food supply; prices of agricultural output; and the level of public and private aids to flood victims within the study area. A sample of households and market leaders were interviewed for the purpose of data collection. Data was equally sourced from Non-governmental Organizations, State Emergency Management Agencies, and other written sources. The data was analyzed and presented using simple bar charts. Findings revealed that there is always a gross inadequacy of food supply during the years of devastating floods compared to years of normal annual rainfall. Prices of agricultural products increased by almost 200% and household income declined significantly during the flood disaster years. Findings also revealed that private organizations sometimes render more aids to flood victims than the public sector. To arrest the danger of annual devastating floods in the Benue Valley, the paper recommends better water infrastructure management strategies like the construction of more dams and dredging of River Benue.